Correlation between the Intensity of Helicobacter pylori Colonization and Severity of Gastritis - Hamid Reza Ghasemi Basir; Mehdi Ghobakhlou; Parvin Akbari; Arash Dehghan; Mohamad Ali Seif Rabiei (Gastroenterology Research and Practice)
Background. The most common cause of chronic gastritis is infection with Helicobacter pylori. Identifying the relationship between intensities of colonization and activity of gastritis helps the clinician in more effective treatment and posttreatment follow-ups. Methods. In this cross-sectional study, endoscopic gastric biopsy samples of 544 patients who complained symptoms of dyspepsia for more than three months referring to the laboratory were studied. To determine the colonization rate of H. pylori and other pathological findings, Giemsa and H&E stains were, respectively, used. Results. Among 544 subjects, 47 (8.64%) patients had no gastritis, 203 (37.32%) had mild gastritis, 278 (10.51%) suffered moderate gastritis, and 16 (2.94%) had severe gastritis. In this study, patients with mild H. pylori colonization rates had the highest level of mild activity (33.52%); in contrast, those with severe H. pylori colonization had the highest level of severe activity (43.75%). 93.96% of people with severe H. pylori colonization suffered from moderate and severe chronic gastritis. There is a significant statistical relationship between the intensity of H. pylori colonization and histopathological findings including intestinal metaplasia, atrophy, and lymphoid follicle formation. Conclusions. According to the present study, with increasing intensity of H. pylori colonization, chronicity and activity of gastritis and its complications increase.